Retirement planning decisions: choices between defined and defined contribution plans - Ali, Bruns Susannah; Frank, Howard A. (2019)
As states move toward offering defined contribution retirement plans as an alternative or addition to traditional defined benefit pensions, they need to consider the preferences and long-term consequences for different groups of employees. This study looks at which plan employees choose when given the option of either a defined contribution or defined benefit plan. The strongest driver of that choice is education level where the most educated prefer defined contribution plans and the least educated stay in defined benefit plans. A unique contribution of this study is that we include region of origin as a study and determine that cultural differences influence plan selection. The study also explores the role of sex, age, and tenure. Challenging other studies on financial planning, these findings indicate that sex and age are not significant factors. This research was conducted using data from more than 4,000 employees from Florida International University and an interview with HR professionals. By understanding retirement preferences in a more nuanced way, we can better craft our approaches to retirement security and financial literacy training in public sector organizations. - Reproduced.
Keywords: Pensions